A comparison of feeding practices of caregivers of infants aged 0–6 months residing in urban and rural areas of Limpopo province, South Africa - M.S. Makwela; E. Maimela; C.B. Ntimana; R.G. Mashaba; M.M. Bopape (Clinical Nutrition Open Science, 2025)
S U M M A R Y: Background: Exclusive breastfeeding (EBF) rates in South Africa have remained low for nearly two decades, with 7% in 2003 and 12% in 2008. While the 2016 South Africa Demographic and Health Survey (SADHS) reported an increase to 32% for infants aged 0–5 months, data on breastfeeding practices in urban and rural areas remain limited. Hence, the study aimed to compare feeding practices of caregivers of infants aged 0–6 months residing in urban and rural areas of Limpopo Province, South Africa. Methodology: This was a cross-sectional, facility-based quantitative study. Convenient sampling was used to select 146 caregivers. Data were collected using a structured questionnaire and analysed using SPSS version 29. Chi-square test was applied to determine the relationship at a 95% confidence interval, where a P-value of <0.05 was considered statistically significant. Results: The prevalence of EBF was higher in caregivers residing in rural areas (41% versus 39%), while mixed feeding was prevalent in urban areas (56% versus 52%). Meanwhile, the proposition of mixed feeding increased with the increase in the age of the infants. There was no significant difference in both groups in terms of as age of the caregivers, level of education, home language, and employment status. Breastfeeding practices improve with increasing age of the caregivers. Conclusions: Caregivers who reside in urban areas tend to practice EBF less compared to those in rural areas. Interventions to promote EBF should focus on women living in urban areas. Breastfeeding increases with the increasing age of the caregivers, therefore, educational interventions that focus on best infant feeding practice, including EBF and misconceptions around EBF, should be implemented with a special focus on younger caregivers.